Modernisasi Sistem Administrasi Pajak dan Sanksi Perpajakan sebagai Determinan Kepatuhan Wajib Pajak Kendaraan Bermotor - Ani Nuraeni; Ade Sudarma (Universitas Muhammadiyah Metro, 2026)
This study aims to determine and explain the modern tax administration system and tax sanctions affect the Compliance of Motorized Vehicle Taxpayers at the Samsat Office of Sukabumi Regency. The results of testing the hypothesis using the t-test variable X1 show that the significance value is 0.001 <0.05, then this shows that Ha is accepted and Ho is rejected, the t-test variable X2 shows that the significance value is 0.228 > 0.05, so this shows that Ho is accepted and Ha is rejected , therefore the modern tax administration system has a positive effect on motor vehicle taxpayer compliance while tax sanctions do not have a positive effect on motor vehicle taxpayer compliance at the Samsat office in Sukabumi district. The results of the F test show that the significance value is 0.002 <0.05, which means that Ha is accepted and Ho is rejected. It can be concluded that the independent variables simultaneously have a significant effect on the compliance variable. The test results for the coefficient of determination show a result of 0.123 or 12.3%, which means that the X variable affects the Y variable by 12.3% while 88.7% is influenced by other factors that are not present in this study.